The spalt gene links the A/P compartment boundary to a linear adult structure in the Drosophila wing. - Sturtevant, M.A.; Biehs, B.; Marin, E.; Bier, E. (Development, 1997)
During Drosophila embryogenesis, each segment is subdivided into an anterior and a posterior compartment through the action of the engrailed gene. Compartmental boundaries bisect imaginal disc primordia which give rise to adult appendages. In early larval development, a short-range Hedgehog signal originating from the posterior compartment of the imaginal wing disc activates expression of genes including decapentaplegic (dpp) in a stripe running along the anterior-posterior compartment boundary. Secreted Dpp emanating from the A/P boundary of wing discs then acts as a secondary signal to organize the wing over large distances. The transcription factor encoded by spalt major (salm) gene, which is expressed in a broad wedge centered over the dpp stripe, is one target of Dpp signaling. In this manuscript, we show that the anterior edge of the salm expression domain abuts a narrow stripe of rhomboid (rho)-expressing cells corresponding to the L2 longitudinal vein primordium. hh mis-expression along the anterior wing margin induces a surrounding domain of salm expression, the anterior edge of which abuts a displaced rho L2 stripe. salm plays a key role in defining the position of the L2 vein since loss of salm function in mosaic patches induces the formation of ectopic L2 branches, which comprise salm- cells running along clone borders where salm- cells confront salm+ cells. These data suggest that salm determines the position of the L2 vein primordium by activating rho expression in neighboring cells through a locally non-autonomous mechanism. rho then functions to initiate and maintain vein differentiation. We discuss how these data provide the final link connecting the formation of a linear adult structure to the establishment of a boundary by the maternal Bicoid morphogen gradient in the blastoderm embryo.